2011
DOI: 10.1007/s11418-011-0539-5
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhiza glabra (Linn.) and Lavandula officinalis (L.) cell suspension cultures-based biotransformation of β-artemether

Abstract: The biotransformation of β-artemether (1) by cell suspension cultures of Glycyrrhiza glabra and Lavandula officinalis is reported here for the first time. The major biotransformed product appeared as a grayish-blue color spot on thin-layer chromatography (TLC) with transparent crystal-like texture. Based on its infrared (IR) and (1)H nuclear magnetic resonance (NMR) spectra, the product was characterized as a tetrahydrofuran (THF)-acetate derivative (2). The highest conversion efficiencies of 57 and 60% were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the continuation of our earlier biotransformation studies on bioactive compounds (Patel et al, 2010(Patel et al, , 2011 http://dx.doi.org/10.1016/j.phytochem.2014.08.004 0031-9422/Ó 2014 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 91%
“…In the continuation of our earlier biotransformation studies on bioactive compounds (Patel et al, 2010(Patel et al, , 2011 http://dx.doi.org/10.1016/j.phytochem.2014.08.004 0031-9422/Ó 2014 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 91%
“…The major biotransformation product was characterized as a tetrahydrofuran (THF) -acetate derivative. This was an effort to synthesize more effi cient artemisinin derivatives/analogs with improved clinical effi ciency (Patel et al 2011 ). Other report on Glycyrrhiza showed that extracts of its cell culture possessed a similar anti-infl ammatory effect to those of fi eld-cultivated equivalent, through the enhancement of the superoxide dismutase activity of plasma and liver tissues.…”
Section: Production Through Unorganized/organized Culturesmentioning
confidence: 99%